Biology of Interleukin-17 and Its Pathophysiological Significance in Sepsis - Ge, Yun; Huang, Man; Yao, Yong-ming (Frontiers in Immunology, 2020)
The interleukin (IL)-17 family includes six structure-related cytokines (A-F). To date, majority of studies have focused on IL-17A. IL-17A plays a pivotal role in various infectious diseases, inflammatory and autoimmune disorders, and cancer. Several recent studies have indicated that IL-17A is a biomarker as well as a therapeutic target in sepsis. In the current review, we summarize the biological functions of IL-17, including IL-17-mediated responses and signal transduction pathways, with particular emphasis on clinical relevance to sepsis.